The limits of possibility: a critical review of C. Crouch, D. Finegold and M. Sako (1999) Are skills the answer? The political economy of skill creation in advanced industrial societies - Lloyd, C; Payne, J (ESRC Centre on Skills, Knowledge and Organisational Performance (SKOPE), 2000)
The paper presents a critical review of Crouch et al.'s Are Skills the Answer? Whilst recognising the book's strengths, attention is drawn to certain problems with its theoretical analysis, including the definition, use and measurement of skill, and a failure to adequately theorise the state, the role of management and the nature of workplace relations. Issue is also taken with what are felt to be the weaknesses of the authors' policy recommendations for a viable high skill strategy. It is argued that the book is symptomatic of a wider tendency in the academic community to confine analysis within the narrow parameters fashioned by policy makers. The paper concludes by calling for a more radical high skill strategy and highlights the need for further research to develop a more convincing political economy of skill.